GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN KURIKULUM MERDEKA - Neliwati Neliwati; Rizky Sembiring Depari; Ikhwan El Musthofa (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Abstract Implementing an independent curriculum in schools requires the right leadership style of the school principal to ensure its success. This research aims to analyze the leadership style of school principals in implementing the independent curriculum. The research method used is a case study of two schools that have successfully implemented the independent curriculum. The research results show that the school principal's leadership style that is effective in implementing the independent curriculum is a transformational leadership style. The principal inspires and motivates teachers to innovate in the learning process, empowers teachers to develop creativity, and encourages students' active participation in learning. Apart from that, the school principal also applies a participative leadership style by involving teachers, parents and other stakeholders in making decisions regarding the independent curriculum. The findings of this research can be a reference for school principals in developing an appropriate leadership style to support the successful implementation of the independent curriculum in schools.